The Cross-Sector Collaboration for Development Policy of Rural Creative Economy: The Case of Bengkoang Creative Hub - Rosyadi, Slamet; Sabiq, Ahmad; Ahmad, Abdul Aziz; Yamin, Muhammad (Journal of Governance and Public Policy, 2021)
This paper examines a cross-sector collaborative model for development policy in a creative economy in a rural area setting. The creative economy based on the villageâ€™s creative potential is considered capable of contributing to the national economy, but it should be supported by public policies that are adaptive to the potential and needs of creative economy actors. The paper used a qualitative approach with case studies in Banyumas Regency, Central Java, Indonesia. This village represents one of the leading creative economy subsectors in Indonesia, which is culinary. The study found that collaboration among Penta Helix forces played multiple roles in driving rural creative actors and building rural creative ecosystems. The stages of collaboration were identified in strengthening organizational structure, program implementation, and organizational consolidation.Â  Organizational capability and innovation have been growing in rural creative economy actors during cross-sector collaboration implementation. This study provides insights into how Penta Helix collaborates with rural creative actors to promote the rural creative economy. From a public policy perspective, this study fills a significant gap in the literature regarding rural development models that are not covered much in the creative economy policy.